2022
DOI: 10.1080/21655979.2022.2053810
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0017639 regulates cisplatin resistance and tumor growth via acting as a miR-1296-5p molecular sponge and modulating sine oculis homeobox 1 expression in non-small cell lung cancer

Abstract: Cisplatin (DDP)-induced chemoresistance is an important reason for the failure of non-small cell lung cancer (NSCLC) treatment. Circular RNAs (circRNAs) participate in the chemoresistance of diverse cancers. However, the function of hsa_circ_0017639 (circ_0017639) in the DDP resistance of NSCLC is unclear. Forty-one NSCLC samples (21 DDP-resistant samples and 20 DDP-sensitive samples) were utilized in the research. The relative expression levels of some genes were determined by real-time quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…We revealed that hsa_circ_0086735 contributed to the resistance of tamoxifen. miR-1296-5p inhibitor has been discovered to restore the decreased cisplatin resistance in cisplatin-resistant non-small cell lung cancer cells (Chang et al, 2022). In this study, miR-1296-5p inhibitor restored the tamoxifen resistance in ZR-75-1 Tam1 cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We revealed that hsa_circ_0086735 contributed to the resistance of tamoxifen. miR-1296-5p inhibitor has been discovered to restore the decreased cisplatin resistance in cisplatin-resistant non-small cell lung cancer cells (Chang et al, 2022). In this study, miR-1296-5p inhibitor restored the tamoxifen resistance in ZR-75-1 Tam1 cells.…”
Section: Discussionmentioning
confidence: 69%
“…MiR-1296-5p has been reported to decrease ERBB2-positive breast cancer and exerts a tumor-suppressive function in breast cancer (Chen et al, 2017). The other known circRNAs that can target miR-1296-5p include hsa_circs_0000517, hsa_circ_0017639, and circ_ 0048764 (Zang et al, 2020;Chang et al, 2022). STAT1 was verified to accelerate breast cancer via deregulating homeostasis of the tumor microenvironment (Zellmer et al, 2017;Hou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that circRNAs control cellular processes through several mechanisms which include modulating transcription ( 23 ), serving as sponge for miRNAs ( 134 ), acting as a platform or sponge for proteins ( 65 ), regulating splicing at the same locus ( 22 ), forming functional circRNA-protein complexes ( 65 ), directly binding to mRNAs to regulate their expression, outcompeting linear mRNAs for protein binding and encoding peptides ( 5 , 146 ). However, a vast majority of reports in drug resistance-associated circRNAs have focused on their function as miRNA sponge ( 107 , 119 ). Further investigations are needed to elucidate involvement of other molecular mechanisms of circRNAs in NSCLC drug resistance.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…found that circ_0017639 silencing inhibited tumor growth and enhanced CDDP sensitivity in vivo . Meanwhile, circ_0017639 also promoted apoptosis and suppressed proliferation, invasion, and migration of CDDP-resistant NSCLC cells via miR-1296-5p/SIX1 axis in vitro ( 107 ). These results indicate that circRNAs are supposed to be the functional biomarkers and novel therapeutic targets for NSCLC.…”
Section: Specific Drug Resistance Associated With Circrnas In Nsclcmentioning
confidence: 99%
“…circRNA-SFMBT2 (hsa_circ_0017639) is a circular RNA transcript originating from the host protein-coding gene SFMBT2. Recently, circRNA-SFMBT2 was reported to function as a tumor promoter in gastric cancer [ 24 ], non-small lung cancer [ 25 , 26 ], and acute myeloid leukemia [ 27 ]. However, little is known about its regulatory role in other tumor types.…”
Section: Introductionmentioning
confidence: 99%